The enterprise potential, individual entrepreneurial orientation and entrepreneurial intentions of students in Serbia - Rajković, Jelena; Poštin, Jasmina; Konjikušić, Marko; Jagodić Rusić, Aleksandra; Stojković, Hadži Strahinja; Nikolić, Milan (The European Journal of Applied Economics, 2021)
In this paper are given the findings of the research of the effects of five variables on the enterprise potential, individual entrepreneurial orientation and entrepreneurial intentions of students. The effects of the following variables are observed: gender, one of my parents has a private business, the year in which the student is studying, student success in learning and studying and the financial opportunities to start a new business. The respondents are studying at seven faculties in Serbia. The sample included 488 respondents.. The most influential variable on entrepreneurial intentions is the financial opportunities to start a new business. Also, men have more pronounced entrepreneurial intentions. Success in studies positively influences entrepreneurial potentials and pro-activity, while the possession of finance positively influences entrepreneurial intentions and risk readiness. In cases of successful studies and the possession of finance, women are more motivated, more determined, and have more pronounced entrepreneurial intentions (especially in the case of having financial resources). Although men may show a preference to become entrepreneurs, women approach entrepreneurship more realistically and decisively.